2011
DOI: 10.1038/onc.2011.318
|View full text |Cite
|
Sign up to set email alerts
|

Human homolog of Drosophila expanded, hEx, functions as a putative tumor suppressor in human cancer cell lines independently of the Hippo pathway

Abstract: The Hippo signaling network is proving to be an essential regulator within the cell, participating in multiple cellular phenotypes including cell proliferation, apoptosis, cell migration and organ size control. Much of this pathway is conserved from flies to mammals; however, how the upstream components, namely Expanded, affect downstream processes in mammalian systems has remained elusive. Only recently has human Expanded (hEx), also known as FRMD6 or Willin, been identified. However, its functional significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
1
35
1
Order By: Relevance
“…Polymorphisms associated with Alzheimer's disease [117], CCL: downregulation leads to resistance to Taxol I MC10FA cells [118] Not studied…”
Section: Frmd6 Human Expandedmentioning
confidence: 99%
“…Polymorphisms associated with Alzheimer's disease [117], CCL: downregulation leads to resistance to Taxol I MC10FA cells [118] Not studied…”
Section: Frmd6 Human Expandedmentioning
confidence: 99%
“…2). Interestingly, rs401681 -TERT/CPTL1M , a variant strongly associated with low-grade and low-risk UBC [38] , was found to be associated with a lower expression of FRMD6 in our study, a gene that was reported to be involved in the inhibition of proliferation in human cells [39] .…”
Section: Individual and Pair-wise Analysesmentioning
confidence: 78%
“…Overexpression of FRMD6 in MDA-MB-231 and MDA-MB-436 breast cancer cells suppresses cell proliferation and up-regulates their sensitivity to chemotherapeutic drug Taxol [20] . Therefore, we tested the anti-proliferative ability of the T28A mutant of FRMD6.…”
Section: T28a Mutant Of Frmd6 Obtaining Stronger Anti-proliferation Ementioning
confidence: 99%
“…Knockdown of FRMD6 in MCF10A cells induces Epithelial-Mesenchymal transition (EMT) [19] . Overexpression of FRMD6 in MDA-MB-231 and MDA-MB-436 breast cancer cells suppresses cell proliferation and upregulates their sensitivity to chemotherapeutic drug Taxol [20] . Although we have already known that FRMD6 functions as a tumor suppressor via the Hippo pathway, the regulatory mechanism on FRMD6 still remains elusive.…”
Section: Introductionmentioning
confidence: 99%